The Impact of Environmental Sanitation on Community Health - Linda Marni; Aulia Asman; Armaita Armaita; Erpita Yanti; Yessy Aprihatin (Science and Environmental Journal for Postgraduate, 2020)
This study aims to describe and discuss the impact of environmental sanitation on public health. The research method used is descriptive. The sampling technique uses purposive sampling. The results showed that: 1) the environmental sanitation conditions of the community were not good because they did not meet health requirements, 2) there was a relationship between the condition of the sewerage, landfills, latrines, and the condition of the house that was not yet healthy so that it had an impact on illnesses such as fever bleeding, tuberculosis, diarrhea and others.